A behavioral perspective on corporate dividend policy: evidence from France. Issue 1 (13th September 2018) - Trabelsi, Dhoha; Aziz, Saqib; Lilti, Jean-Jacques
Abstract : Purpose: This paper empirically examines the catering theory of Baker and Wurgler (2004 ) in the particular context of France. Considering the characteristics of French market – known for its high concentration of capital – it attempts to highlight the role family control plays in the managerial tendencies to satisfy non-informative dividend demands. Design/methodology/approach: The paper focuses on a large data set of French firms included in the SBF-250 index over a period of 1992-2010. It uses a variety of dividend policy measures, including dividend premium, percentage of dividend-paying firms and probability of paying dividends. It adopts appropriate empirical specifications (time-series and probit models) to substantiate the research hypotheses. Findings: The empirical findings show that the percentage of payers rises with the dividend premium, and that the dividend premium and the confidence index of French households are negatively correlated. This reflects the sensitivity of dividend demand to investor sentiment. Moreover, results of multivariate panel regression show a positive and statistically significant effect of the dividend premium on the firm's tendency to pay, after controlling for firm characteristics. Finally, it finds that the dividend premium effect disappears in the case of family-controlled firms. This result is in line with the long-term orientation of family firms. Research limitations/implications: The study focuses on the dividend payment behavior of French firms. Although dividends are deeply engrained in France, authors believe that it will be interesting to look at the whole payout policy and particularly the role played by share repurchases. Practical implications: Addressing short-term catering and managerial opportunism, the results of this study may be of interest for shareholders, potential investors and regulators. Originality/value: To the best of the authors' knowledge, this is the first study that provides empirical evidence on Baker and Wurgler (2004 ) catering theory by considering the particularity of French market where, unlike the US, percentage of dividend-paying firms is high and the corporate ownership structures are different.